Sustainable Management of Medicago sativa for Future Climates: Insect Pests, Endophytes and Multitrophic Interactions in a Complex Environment - McNeill, Mark R.; Tu, Xiongbing; Altermann, Eric; Beilei, Wu; Shi, Shengjing (Frontiers in Agronomy, 2022)
Medicago sativa L. (alfalfa, syn. lucerne) is an important forage crop for livestock, which is subject to attack from a range of insect pests and susceptible to diseases that can reduce production and persistence. This review considers the main insect pests affecting M. sativa in China and New Zealand as well as the wider plant resistance mechanisms and multitrophic interaction that occur between plants, insect pests, entomopathogens, endophytes, the environment and climate change. This is with a view to identifying new research opportunities applicable to M. sativa that can be applied to improving production and persistence of this important agricultural crop. These opportunities include identification and activity of entomopathogens/endophytes (e.g., Bacillus and Pseudomonas spp., Metarhizium spp.) and plant growth enhancers (Trichoderma), as well as multitrophic plant-insect-microbial interactions.